Intellectual disability. What do we know? - Yleana Ferrat Clark; Marta Amelia Hernández Martínez (Acta Médica del Centro)
Introduction: intellectual disability implies special needs in the individuals who suffer from it and constitutes a health problem that affects patients, family members and the community because it generates a great impact on health and social systems. Objective: compile updated information on intellectual disability, types, characteristics and causes, among other aspects of interest for professionals who care for people with intellectual disabilities. Methods: a bibliographic study was carried out for which 43 publications available in Google Scholar were reviewed, all after 2015 (19 journal articles, 13 websites, five textbooks, three theses and three regulatory documents). Development: the information obtained was organized as follows: generalities, some historical considerations, definition of intellectual disability, classification, characteristics of the different degrees of intellectual disability, psychological characteristics, particularities of personality formation, characteristics of the emotional sphere volitional and interventions. Conclusions: people who present difficulties in the intellectual sphere should receive individualized attention, the importance of intervening in the training of people with this disability was evident in order to achieve their insertion into the family and social context, as well as their independence.